KICK ASYMMETRY ALONG A STRONG MAGNETIC FIELD IN THE PROCESS OF NEUTRINO SCATTERING ON NUCLEONS - Ognev, I. S.; Gvozdev, A. A. (Одеські астрономічні публікації, 2017)
The neutrino-nucleon scattering in a collapsing star envelope with a strong magnetic field is investigated. The transferred momentum asymmetry along the field direction is obtained. It is shown that neutrino-nucleon scattering gives a contribution to the asymmetry comparable with direct URCA processes. Hence, neutrino-nucleon scattering should be taken into account in estimations of a possible influence of neutrino reemission processes on a collapsing star envelope dynamics.